Memorizing The Qur’an as a Formation of Self-Identity - Jannah, Raudatul; Hasanah, Mila; Norlaila, Norlaila; Norjamilah, Norjamilah; Rasyidi, Ahmad (Jurnal Pendidikan Islam, 2025)
The rapid flow of modernization and global challenges make strengthening self-identity very crucial. Students who memorize the Qur’an occupy a strategic role in society as agents who are expected to be able to bring progress without abandoning the Islamic values taught in the Qur’an. This study aims to analyze students’ Qur’an memorization activities that contribute to the formation of self-identity. This is very important in order to instill and develop self-understanding, values and the role of students who memorize the Qur’an in society. This research was prepared with a phenomenological approach to explore meaning through the process of social interaction that occurs in society with the aim of seeing the extent to which self-identity has been realized in students who memorize the Qur’an in their daily activities. The subjects in this study are tahfizh students in Banjarmasin, including asatidz and asatidzah who manage student tahfizh dormitories in the city of Banjarmasin. The results of this study show that interest and environmental factors have a great influence in building motivation and positive image of tahfizh students in forming their identity as memorizers of the Qur’an. This research is useful to develop a model and framework that describes the mechanism of tahfizh activities that contribute to the fertilization of self-identity as memorizers of the Qur’an which will later have an important contribution in society so that memorazing Qur’an are not only used as a symbol that is feared to cause religious commodification.